The 1984 GM Agreement in Canada: Significance and Consequences - Benedict, Daniel (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
The 1984 negotiations and strike at General Motors in Canada are a turning point in the relations between US and Canadian unions. The different elements of the crisis are explained by the author who also raises possible consequences on the future of the Canadian labour movement.